Music Creation Wajaprani | Tabuh Kreasi Wajaprani - Surya Adinatha, Made Surya; Andayani, Ni Putu Tisna (GHURNITA: Jurnal Seni Karawitan, 2024)
Coral rocks, as an iconic element of Bali's coast, have a central role in the island's art and culture. Music, musical arts and dance in Bali often use the character and unique shapes of coral rocks found along the coast to become inspiration for works of art. In Jembrana district, precisely in Pengeragoan village, there is Yeh Leh Beach, on this beach there are beautiful coral rocks which later became the inspiration for the creation of the creative percussion work entitled Wajaprani. The rock's sturdy character even when hit by waves is an inspiration for creating dynamic rhythms. with the character of the coral rocks on Yeh Leh Beach, the stylist thought it would be very suitable to use the medium of gamelan gong kebyar to implement the characters on the coral rocks.